Sign fetishism and allegorical interruption - García Elizondo, Eduardo (2025)
This paper explores the rhetorical intersection between sign fetishism and allegorical interruption in Walter Benjamin’s critique of the philosophy of art’s discourse. To achieve this goal, it uses an expository interpretation to focus on the discursive moments that bring the phantasmagoric representation of signs into a dialectical tension with an allegorical, materialist reading of an indiciary type. In the conclusions, I discuss how this dialectical tension plays out in relation to the staging of historical temporality and its rhetorical-aesthetical reliefs.